Aplikasi Pembentukan Akronim Dalam Bahasa Indonesia Bagi Siswa MAS PROYEK Universitas Alwashliyah Medan - Susy Deliani; Hasnil Aida Nasution; Nurhayati Nasution (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
This Community Service was carried out at the UNIVA Medan MAS Project in June 2021, the background of this PKM is remembering that the UNIVA Project MAS students are the next generation of the nation who must be equipped with the spirit of Love and uphold Indonesian as the National Language and Language of Unity. Indonesian treasury is the wealth and ability of a language to meet the needs of its speakers. An acronym is an abbreviation that is pronounced as a natural word and the function of an acronym is the same as a word in Indonesian. The rapid and unstoppable growth and development of acronyms requires guidelines or rules to ensure that acronyms that are entered into Indonesian match the pattern of acronym formation in Indonesian. The method used in this PKM is in accordance with the steps of scientific work, namely: 1) Situation analysis, 2) Implementation design, 3) implementation, 4) Evaluation of PKM results and 5) PKM report. The results of the implementation of PKM showed that there were significant changes to the MAS students of the UNIVA Project.